Promosi Pariwisata Bali dan Queensland melalui Film “Ticket to Paradise” - Bestari, Ni Made Prasiwi (Humanis; Vol 27 No 2 (2023)DO - 10.24843/JH.2023.v27.i02.p04, 2023)
The film industry and tourism have a very strong relationship, which can benefit one another. Various tourist destinations use films to promote their area and attract tourists. There are also many films made in tourism destinations and showcase these destinations, so as to attract tourists to visit them. As a world popular destination, Bali has been choosen by several film producers to make film here such as the international box office movie “Eat Pray Love” (2010) and the most recent one is “Ticket to Paradise” (2022). The story of “Ticket to Paradise” sets in Bali but did not shoot here, instead in Queensland Australia because of the Pandemic Covid-19. This study aims to analyze the benefits of film "Ticket to Paradise" for Bali and Queensland tourism tourism industry The analysis was carried out using interpretive qualitative methods in investigating the tourism symbols contained in the film.  In terms of the storyline, dialogue and visuals contained in this film, this study concludes that the film "Ticket to Paradise" both promotes the tourism industry in Bali and Queensland, although the promotional impact will be more optimal if the film is made and shot in Bali.